Pengaruh Kompensasi, Lingkungan Kerja, Gaya Kepemimpinan, dan Motivasi Terhadap Produktivitas Kerja Karyawan - Dwi Nur Indah Sari; Ika Wulandari (Journal of Trends Economics and Accounting Research, 2024)
Human resources is considered as an importantresource for the organization, because without qualified human resources, the organization will not be able to survive in the competition. The purpose of this study was to determine the ieffect iof compensation, work environment, leadership style and motivation on employee productivity in CV Larasati Abadi Jaya Temanggung partially and simultaneously. Data collection techniques by questionnaire distributed to respondents are iemployee of CV Larasati Abadi Jaya Temanggung throughtout the department. The analytical tool used is multiple linear regression, and T test. The population considered was 130 employes CV Larasati Abadi Jaya Temanggung. By calculating using the Slovin formula and getting sample results from 60 respondents. The result showed that Y + e, with value of constanta is 12,775. According to the t-tes, the compensation has no influence on work productivity, work environment has no influence on work productivity, leadership style has no influence on work productivity, and motivation has an impact on work productivity.